Mutações em genes de predisposição para câncer de mama em pacientes brasileiros de risco - Sás, Daíse Moreno [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Breast cancer is the most common form of cancer and the second most common cause of death from a neoplastic disease affecting women. There are a number of recognized risk factors for the development of breast cancer including hereditary factors, hormonal, reproductive and menstrual history, age, lack of exercise, alcohol, radiation, benign breast disease, and obesity. Although approximately 10% to 30% of breast cancer cases are attributed to hereditary factors, only 5% to 10% of cases are identified with a strong genetic component, and only a small fraction of these (4% to 5%) are explained by mutations in high penetrance genes in an autosomal dominant inheritance. Most cases of hereditary breast cancer are attributed to germline mutations in high penetrance genes BRCA1 and BRCA2 that are responsible for Breast Cancer Ovary Syndrome the hereditary. Several studies have identified other susceptibility genes for breast cancer with high penetrance, but some cases of strong evidence for a hereditary syndrome as a cause of breast tumors the result is negative for mutations in these genes. Recently, other genes and common polymorphic markers were also associated with small or moderate increase in risk for breast cancer. The next generation sequencing (NGS) allows the analysis of multiple genes simultaneously in tests on panels format whit a reduced cost compared to sequencing by the Sanger methodology. However, relevant clinical information about variants found in these extended tests have not kept the same pace of sequencing technology. Important information such as penetrance genetic variants (in particular, missense variants) and the appropriate clinical management of carriers of these mutations are not availabe. The aim of this study was to evaluate the occurrence of genetic changes in 17 breast cancer predisposition genes in Brazilian risk patients, suitable for genetic testing. Genetic testing included analysis of the DNA of patients using...

O câncer de mama é a forma mais comum de câncer e a segundo causa mais comum de morte por uma doença neoplásica afetando mulheres. Há uma série de fatores de risco reconhecidos para o desenvolvimento do câncer de mama incluindo fatores hereditários, hormonais, reprodutivos e história menstrual, idade, falta de exercício, álcool, radiação, doença benigna da mama, e obesidade. Embora aproximadamente 10% a 30% dos casos de câncer de mama sejam atribuídos a fatores hereditários, apenas 5% a 10% dos casos são identificados com um componente hereditário forte, e apenas uma pequena fração desses (4% a 5%) são explicados por mutações em genes de alta penetrância em uma herança autossômica dominante. Grande parte dos casos de câncer de mama hereditário são atribuídos a mutações germinativas nos genes de alta penetrância BRCA1 e BRCA2, responsáveis pela Síndrome de Câncer de Mama o Ovário Hereditários. Vários estudos têm identificado outros genes de susceptibilidade para o câncer de mama com alta penetrância, mas alguns casos de forte indício para uma síndrome hereditária como causa dos tumores de mama o resultado é negativo para mutações nestes genes. Recentemente, outros genes e marcadores polimórficos comuns também foram associados com aumento pequeno ou moderado no risco para câncer de mama. O sequenciamento de nova geração (NGS) permite analisar múltiplos genes simultaneamente em testes no formato de painéis, a um custo reduzido em comparação com o sequenciamento pela metodologia de Sanger. No entanto, informações clínicas relevantes sobre as variantes encontradas nestes testes estendidos não mantiveram o mesmo ritmo da tecnologia de sequenciamento. Faltam informações importantes como a penetrância das variantes genéticas (em particular, de variantes missense) e o manejo clínico adequado dos portadores destas mutações. O objetivo do presente estudo foi avaliar a ocorrência de...
Keywords: Mamas - Cancer; Mutagenese; Doenças hereditarias; Análise de DNA; Pacientes - Pesquisa; DNA - Analysis